2022
DOI: 10.3389/fnhum.2022.954898
|View full text |Cite
|
Sign up to set email alerts
|

Widespread cortical thinning, excessive glutamate and impaired linguistic functioning in schizophrenia: A cluster analytic approach

Abstract: IntroductionSymptoms of schizophrenia are closely related to aberrant language comprehension and production. Macroscopic brain changes seen in some patients with schizophrenia are suspected to relate to impaired language production, but this is yet to be reliably characterized. Since heterogeneity in language dysfunctions, as well as brain structure, is suspected in schizophrenia, we aimed to first seek patient subgroups with different neurobiological signatures and then quantify linguistic indices that captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…More recent work in treatmentresistant subjects indicate that ACC glutamate could in uence subcortical substrates of reward learning, thus providing further mechanistic link to negative symptoms [40]. This is also consistent with several other observations based on genetic [41] and structural imaging data [42] linking glutamate aberrations to the broader construct of negative symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…More recent work in treatmentresistant subjects indicate that ACC glutamate could in uence subcortical substrates of reward learning, thus providing further mechanistic link to negative symptoms [40]. This is also consistent with several other observations based on genetic [41] and structural imaging data [42] linking glutamate aberrations to the broader construct of negative symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, ketamine, when administered to patients with prior experience of psychosis, results in the reemergence of AVHs and FTD features in particular 149 . More direct examinations of the glutamate dynamics and FTD in patients are needed 150 , since pharmaco-fMRI studies in healthy participants only provide indirect evidence of the involvement of glutamate in the occurrence of FTD.…”
Section: Neurochemical and Genetic Basis Of Language Abnormalities Ne...mentioning
confidence: 99%
“…We also found that the CPZ equivalent of neuroanatomical subtype 2 (widespread GMV loss) was higher than that of neuroanatomical subtype 1 (focal GMV increase). Previous in vivo and ex vivo MRI and postmortem histological studies suggested that exposure to antipsychotic treatment causes significantly reduced whole brain volume, especially gray matter [ 51 53 ]. Thus, antipsychotic drugs could partially explain the wider brain atrophy in neuroanatomical subtype-2 chronic patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%